Morphology of some fossil lacustrine centric species from the western United States assigned to the genus Cyclotella (Bacillariophyta), including four described as new - Kociolek, J. P.; Khursevich, G. K. (Phytotaxa, 2013)
During consideration of fossil centric diatoms from a variety of non-marine localities in the western USA, we encountered four new species and two previously known taxa that should be assigned to the genus Cyclotella (F.T. Kützing) A. de Brébisson. We detail the morphological features of these species, and discuss their relevance to other members of the Cyclotella. These fossil species are studied in light and scanning electron microscopes, and can be assigned to several morphological groups with respect mainly to the structure of alveolae as well as positon(s) of rimoportula(e) and marginal fultoportulae. Presence of loculate areolae with internal domed cribra and external foramina, or both areolae and valve face fultoportulae in the central area are characteristics found in all of these Cyclotella taxa.